2008
DOI: 10.1055/s-2007-972566
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Burden of Alcohol Intoxication on Pediatric In-Patient Services in Germany

Abstract: This is one of the very few studies that provide epidemiological data on the specific issue of alcohol intoxications in children and adolescents that require in-patient treatment. Apparently, gender differences seem to play a minor role in alcohol-related hospital admissions. Our data demonstrate that excessive alcohol consumption remains an issue of concern in this age cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
2
7
0
1
Order By: Relevance
“…Also, 82.0% of the hospitalizations due to alcohol intoxication were in the age group 14-18 and the number of hospitalized children in that age group has alarmingly grown over the years. Similar results were reported by a German study, with greatest increase in hospitalizations due to alcohol intoxication in the adolescents aged between 13 and 17 (20). A Polish study showed that 37% of children first tried alcohol when they were between 10 and 15 years old.…”
Section: Discussionsupporting
confidence: 86%
“…Also, 82.0% of the hospitalizations due to alcohol intoxication were in the age group 14-18 and the number of hospitalized children in that age group has alarmingly grown over the years. Similar results were reported by a German study, with greatest increase in hospitalizations due to alcohol intoxication in the adolescents aged between 13 and 17 (20). A Polish study showed that 37% of children first tried alcohol when they were between 10 and 15 years old.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the study presented by Selma H. Bouthoorn et al [1], we demonstrated in a national German study, that the number of alcohol-intoxicated children and adolescents requiring in-patient hospital treatment (≥24 h) increased significantly in the years 2000-2002, the most prominent increase being seen in adolescents aged 13-17 years, and female patients [4]. The percentage of female patients increased from 34.1% in 2000 to 41.9% in 2001 and 49.8% in 2002 (p*<0.05).…”
supporting
confidence: 89%
“…Once realised, these intervention measures then mandate ongoing assessment as to whether they improve the outcomes of this group of children and adolescents. While these measures have to take into consideration gender differences in the susceptibility to alcohol consumption-as shown by the study from Bouthoorn et al [1], health care workers should also be prepared to see an increasing influx of female adolescents [4].…”
mentioning
confidence: 99%
“…While excessive alcohol consumption in adolescence, especially binge drinking, has been comprehensively investigated (for a review, see Courtney and Polich [20]), acute alcohol intoxication with subsequent hospital admission (i.e., BIHA) as an extreme form of bingeing has gained scientific attention only during the last years [3,4,21,22,23,24,25,26,27]. An important question concerning the significance of extreme bingeing remains open: does a single BIHA indicate that psychosocial development is at risk, e.g., by the development of AUDs?…”
Section: Introductionmentioning
confidence: 99%